Howard Pyle's Book of Pirates : Fiction, Fact & Fancy Concerning the Buccaneers & Marooners of the Spanish Main - Pyle, Howard, 1853-1911 (Salt Lake City, UT : Project Gutenberg, 2006)
"Howard Pyle's Book of Pirates" by Howard Pyle is a historical fiction work, rich in tales and illustrations concerning the infamous buccaneers and marooners of the Spanish Main, compiled in the late 19th century. The narrative aims to capture the audacious exploits and the tumultuous lives of these seafaring rogues, evoking the history and folklore associated with piracy. The opening of the book sets the stage with a sweeping introduction to the world of pirates, detailing their origins and the dark allure surrounding them. It begins with a historical perspective, discussing the ruthless activities of early buccaneers, who roamed the Caribbean seeking treasure and glory. Pyle paints vivid scenes of adventure and treachery, introducing characters such as Captain Morgan and other notorious figures of the piracy era. The reader is immersed in the grim realities of pirate life, from swashbuckling battles to the insatiable quest for wealth, piquing interest in the tales that will follow in the subsequent chapters. (This is an automatically generated summary.)
Release date is 2006-02-05
Produced by Charles Keller and David Widger
Keywords: Spanish Main -- Fiction; Pirates -- Fiction; Sea stories, American; Buccaneers -- Fiction; Historical fiction, American